A New Graph-Analytical Method for Kinematic Analysis of Spatial Mechanisms - Mustafayev, M.R.; Panakhova, N.D.; Yakhyaeva, A.N. (Herald of Azerbaijan Engineering Academy, 2022)
The article considers the definition of the kinematic parameters of a four-bar spatial mechanism. For this purpose, a new graph-analytical method based on a three-dimensional computer model is applied. A new analytical dependence between the parameters of the mechanism is obtained and the kinematic parameters of the mechanism are calculated from it. The advantages of the proposed method and the reliability of the obtained results are confirmed by comparing reliable data obtained by the graphical method.